ANALYSIS OF FEASIBILITY OF DEVELOPMENT OF AGROPOLITAN AREA PROBOLINGGO DISTRICT - Markus Patiung (Socio-Economics/Agribusiness Department, 2021)
This research was conducted in Probolinggo district, East Java Province, Indonesia. The research objective was to analyze the feasibility of developing an agropolitan area from the financial and infrastructure aspects. The analytical methods used are: Revenue Cost Ratio analysis; Payback Period (PP); Net Present Value (NPV); Internal Rate of Return (IRR). The results showed that the development of the farmer's market, namely the development of the Krucil fruit and vegetable market, the construction of a flat storage market and the development of the leaning agribusiness sub-terminal, and infrastructure are very feasible to build in the context of developing an agropolitan area and need to be continued in the Detail Engineering Design (DED).